Phenological Assessment for Agronomic Suitability of Some Agastache Species Based on Standardized BBCH Scale - Rodica Vârban; Andreea Ona; Andrei Stoie; Dan Vârban; Ioana Crișan (Agronomy, 2021)
Increasing interest in medicinal plants encourages the growers to consider extending their range of cultivated species. Acclimatization and adaptation of species introduced for cultivation in new areas remain a challenge of modern agriculture. One of the first steps for optimizing the cultivation technology is determining the plant phenology in the local conditions. Therefore, the aim of this research was to provide a standardized phenology scale for Agastache sp. and to apply it in assessing the suitability for cultivation in a local environment of some valuable Agastache species: Agastache scrophulariifolia, Agastache rugosa, Agastache mexicana, Agastache foeniculum and Agastache rugosa ‘After Eight’. During the vegetation period, nine growth stages were identified: germination/emergence, leaf development, formation of side shoots, stem elongation, inflorescence emergence, flowering, fruit development, fruit maturity, senescence and beginning of resting. Observations conducted over two years revealed that the vegetation period increased from 168.8 ± 3.51 days in the first year to 199.0 ± 1.82 days in the second year. In both vegetation periods, the flowering phenophase predominated, but the abundance of precipitations shortened the flowering duration in the second year. The duration of phenophases was highly influenced by growing degree days. Phenological assessment based on a standardized scale can be a useful tool for evaluating cultivation potential and the planning of technological resources.